A perspectiva da inteligência competitiva como um recurso estratégico - Buzzerio, Felipe Gama (2012)
The purpose of this research was to investigate the Competitive Intelligence (CI) by itself as a potential source of competitive advantage, based upon the Resource Based View (RBV) framework. Therefore, the main concepts of the available literature were organized in the following sequence in order to support the research: strategic management, strategic resources, RBV main concepts, competitive advantage, strategic resources main characteristics and competitive intelligence. The research method employed in this study was exploratory qualitative descriptive, making use of deep interviews guided by a semi structured script. In total, six executives in charge of CI functions from different companies were interviewed. It is relevant to highlight that none of these companies were competitors whatsoever, in order to keep the proper protection and privacy of their competitive information. Content analysis method was selected to analyze the obtained data (BARDIN,2006). The main result identified was the impossibility of considering CI by itself as a source of competitive advantage from the RBV perspective. The main explanation is that CI does not fit into all of the Barney and Hesterly (2007) VRIO (Value, Rarity, Imitability,Organization) aspects at the same time and conditions such model has served as a basis to evaluate CI as a possible strategic resource. However, there were indications that CI could be considered rare, difficult to imitate, and dependent on organizational conditions to maximize its potential. Notwithstanding, there were no indications that CI could generate value,especially to the customer. This aspect is tightly connected to the competitive advantage concept herein adopted and it is vital in fulfilling this research main goal.